Perbandingan Cara Mencacah Banyak Lintasan Terpendek antara Dua Titik pada Grid - Wiworo Wiworo (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2020)
The problem of counting the number of shortest paths between two points on a grid is a combinatorial problem that is often found in mathematical competitions or enrichment problems for various levels of school. There are several ways to count, namely by drawing a figure (visual representation), by the number pattern in the Pascal Triangle, and the combination formula. This paper discusses a comparison of each ways related to the problem at hand. On a simple grid all of the three methods can be used. On complex grids the combination formula is the only method can be applied, in some cases the technique of number pattern in Pascal Triangle is still applicable. On the grid with varied obstacles, foresight and flexibility is needed in the selection of the counting methods.